Immunoglobulin Y in the diagnosis of Aeromonas hydrophila infection in Nile tilapia (Oreochromis niloticus) - Fernandes, Dayanne C. [UNESP]; Eto, Silas F. [UNESP]; Funnicelli, Michelli I.G. [UNESP]; Fernandes, Camila C. [UNESP]; Charlie-Silva, Ives [UNESP]; Belo, Marco A.A. [UNESP]; Pizauro, João M. [UNESP] (Elsevier, 2019)
Aeromonas hydrophila (Ah) are rod-shaped, Gram-negative, motile aquatic bacteria that can infect fish and mammals, including humans. Due to the importance of this pathogen for fish farming and public health, the present study produced a specific immunoglobulin (Ig) Y by immunizing laying hens with Ah cell proteins. The antibody efficacy in detecting Ah was tested by direct immunofluorescence and indirect immunohistochemistry using tissues from infected Nile tilapia. The produced IgY exhibited specificity and affinity for membrane and cytoplasmic Ah proteins, which enabled detection of the intracellular localization of the bacteria and their proteins within the phagosomes of phagocytes and detection of extracellular bacteria colonizing host tissues. Thus, the findings offer a new perspective on the use of IgY for the diagnosis and analysis of Ah pathogenesis in Nile tilapia.
Keywords: Aeromonosis; Antibody; Immunodiagnosis; Sepsis; Teleost